Isolated Leprosy of Bilateral Ear Lobes, A Rare Presentation of Leprosy - Paudel, V.; Chudal, D. (Kathmandu University Medical Journal, 2021)
Hansen disease is a chronic infectious disease caused by Mycobacterium leprae. It can present with a variety of clinical manifestations depending on the immune status. Ear lobes are commonly involved in leprosy. However, isolated earlobe involvement of both ear lobes is rare. We present a case of a 25-year-old man who presented with isolated swelling of both pinna, which on slit skin smear turned to be multi-bacillary leprosy. The bilateral pinna swelling started as asymptomatic, multiple skin colored shiny papules which progressively became lobular over a period of a year. Isolated involvement of the pinna in a patient without lesions in other body parts is an unusual initial presentation of leprosy. However, leprosy should be kept as a rare differential diagnosis of isolated lesions on the ear in patients not responding to conventional treatment.